Technological tools and collaborative learning in students of a private university in Lima - Cardenas-Mancilla, Paola (2023)
In recent years, technological progress has disruptively entered the educational field, which motivated the present research whose objective was to determine the relationship between technological tools and collaborative learning in students of a private university in Lima, 2023. The research was transversal, basic typology, non-experimental design, correlational level, and, quantitative approach. The population group consisted of 145 students of 1st, 2nd and 3rd cycle, of the first semester of the academic year 2023, the sample was of probabilistic type with a stratified order sampling. To collect the data, the survey technique was used and the questionnaire was used as an instrument for each variable, these were submitted to the judgment of specialists to determine their validity and to measure the reliability Cronbach's Alpha was used, obtaining high reliability indexes. The results showed a prevalence of high level perception among students, with 71% of technological tools and 78% of collaborative learning. It was concluded that there is a direct correlation between technological tools and collaborative learning. In post-pandemic times, technological advances in education play a very important role, because they allow to keep constantly updated through collaborative learning.